Enhanced gelation of sturgeon frozen surimi via egg white: Exploring the role of endogenous serine protease inhibition - Lu Tong; Ning Ding; Meng Zhou; Yan Zhang; Hui Hong; Yongkang Luo; Yuqing Tan (Food Frontiers)
Abstract The degradation of frozen sturgeon surimi can be attributed to the endogenous serine protease. This study was first to examine the impact of egg whites on the frozen sturgeon surimi's gel properties from the perspective of inhibiting endogenous serine protease. The protease activity of egg whites group (CA + EW group, consisting of 4% egg whites and cryoprotectants) was 45.15% lower than that of cryoprotectants group (CA group, consisting of 3% sucrose, 3% sorbitol, and 0.3% sodium tripolyphosphate) at 12 weeks. From the results of inhibition kinetics, serine protease was inhibited by both anticompetitive and noncompetitive inhibition modes. Molecular docking analysis indicated that egg white achieves this inhibitory effect through ionic interactions and hydrogen bonding with serine protease. However, this inhibitory effect was absent when the freezing period was extended to 24 weeks. Compared with CA group, the CA + EW group exhibited 54.76% and 4.59% increase in gel strength and water‐holding capacity, and 32.42% reduction in cooking loss after 24 weeks of freezing. Egg whites also impeded water migration and enhanced the density and smoothness of the gel microstructure, reducing protein aggregation. These results indicated that egg whites serve a dual function: inhibiting serine protease and filling the gel network within 12 weeks, mitigating protein aggregation and ice crystal formation over 24 weeks. This study elucidated the mechanism underlying the impact of egg white on endogenous serine protease in sturgeon surimi during long‐term freezing, laying a theoretical foundation for the industrialization of sturgeon surimi.